Rapid adaptation in phoretic mite development time. Issue 1 (December 2018) - Schedwill, Petra; Geiler, Adrian; Nehring, Volker
Abstract Strong ecological selection can erode genetic variation and render populations unable to deal with changes in ecological conditions. In the adaptation of the phoretic mitePoecilochirus carabi to its host, the burying beetleNicrophorus vespilloides, the timing of reproduction is crucial. Safe mite development is only possible during the beetles' brood care; mites that develop too slowly will have virtually zero fitness. If the strong specialisation in development time leaves no room for standing genetic variation to remain, changes in beetle brood care are disastrous. Beetle brood care depends on temperature and is thus vulnerable to changing climate. Accidental host switches to another beetle species with shorter brood care would also have negative effects on the mites. Only sufficient standing genetic variation could allow mismatched mite lines to survive and adapt. To test whether such rapid adaptation is possible in principle, we artificially selected on mite generation time. We were able to speed up, but not to slow down, mite development. We conclude that there is enough standing genetic variation in development time to allowP. carabi to quickly adapt to new host species or climate conditions, which could potentially lead to the evolution of new mite species.